Overview of Anxiety Levels During English Day Performances Among Students at MAN 2 Kuansing - Susfika Mei Sari Nur; Darwin Karim; Sofiana Nurchayati (Journal of Education Technology Information Social Sciences and Health, 2025)
Anxiety, referred to as anxiety, is an unpleasant emotional state or a feeling of discomfort and restlessness accompanied by autonomic responses (unconsciously known to someone), also leading to a lack of courage and worry about unclear things. The prevalence of depression or anxiety disorders has a relatively high rate among the adolescent population. According to WHO data in 2015, around 4.4% of the world’s population, or 322 million people, experienced depression, and about 3.6% of the world’s population, or 264 million people, experienced anxiety. This research aimed to determine the level of anxiety among students at MAN 2 Kuansing during the English Day event. A quantitative study with a cross-sectional design was conducted. The sample in this study was students from class X and XI at MAN 2 Kuansing using this method, with 71 respondents, and the sampling technique used was convenience sampling. Data was collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire. The data analysis used univariate analysis. The research results showed that the majority of respondents who had anxiety levels based on age characteristics were mainly middle adolescents (15-16 years old), totaling 68 people (95.8%). There were 41 female respondents (57.7%), and highest frequency of classes was from class X1, totaling 38 people (53.5%). The anxiety level in MAN 2 Kuansing students showed that most respondents experienced mild anxiety, with 27 people (38.0%). The level of anxiety among adolescent students at MAN 2 Kuansing showed that most respondents had mild anxiety.